Exploring teachers' behavioural intentions to design artificial intelligence-assisted learning in Chinese K-12 education - Wang, Kai; Chai, Ching-Sing; Liang, Jyh-Chong; Sang, Guoyuan (Technology, pedagogy and education, 2024)
As artificial intelligence (AI) advances rapidly, it has been incorporated into formal education to facilitate subject-based learning. Integration of AI technologies to support learning requires teachers to intentionally design AI-assisted learning. However, there have been a limited number of empirical studies investigating teachers' behavioural intentions to design AI-assisted learning. To explore the predictors of teachers' behavioural intentions to design AI-assisted learning and examine the structural relationships among these factors, the authors constructed a structural model of AI literacy, Technological Pedagogical Content Knowledge (TPACK), technostress, school support, teacher agency, teacher autonomy and behavioural intentions. Data from 312 K-12 in-service teachers in China were analysed. The results suggest that TPACK, school support, teacher agency and teacher autonomy positively predict teachers' behavioural intentions to design AI-assisted learning. However, AI literacy and technostress were not statistically associated with teachers' behavioural intentions. On the other hand, TPACK significantly mediated AI literacy and teachers' behavioural intentions.